An overview of the Australian Centre for Advanced Photovoltaics and the Australia-US Institute for Advanced Photovoltaics. Issue 1771 (2015) - Corkish, Richard; Green, Martin A.; Blakers, Andrew W.; Burn, Paul L.; Cheng, Yi-Bing; Egan, Renate; Ghiggino, Kenneth P.; Meredith, Paul; Scholes, Fiona H.; Wilson, Gerry
ABSTRACT: The Australian Centre for Advanced Photovoltaics (ACAP) co-ordinates the activities of the six Australian research institutions and a group of industrial partners in the Australia-US Institute for Advanced Photovoltaics (AUSIAPV) to develop the next generations of photovoltaic device technology and to provide a pipeline of opportunities for performance increase and cost reduction. AUSIAPV links ACAP with US-based partners. These national and international research collaborations provide a pathway for highly visible, structured photovoltaic research collaboration between Australian and US researchers, institutes and agencies with significant joint programs based on the clear synergies between the participating organizations. The research program is organized in five collaborative Program Packages (PPs). PP1 deals with silicon wafer-based cells, focusing on three main areas: cells from solar grade silicon, rear contact and silicon-based tandem cells. PP2 involves research into a range of organic solar cells, organic/inorganic hybrid cells, "earth abundant" thin-film materials and "third generation" approaches. PP3 is concerned with optics and characterization. PP4 will deliver a substantiated methodology for assessing manufacturing costs of the different technologies and PP5 involves education, training and outreach. The main research topics, results and plans for the future are presented.